2020
DOI: 10.1186/s12879-020-05391-y
|View full text |Cite
|
Sign up to set email alerts
|

Case report: multiple and atypical amoebic cerebral abscesses resistant to treatment

Abstract: Background The parasite Entamoeba histolytica is the causal agent of amoebiasis, a worldwide emerging disease. Amebic brain abscess is a form of invasive amebiasis that is both rare and frequently lethal. This condition always begins with the infection of the colon by E. histolytica trophozoites, which subsequently travel through the bloodstream to extraintestinal tissues. Case presentation We report a case of a 71-year-old female who reported an altered state of consciousness, disorientation, sleepiness and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Amebic brain abscesses are extremely rare and arise almost exclusively alongside amebic lung or liver abscess [ 2 ]. Victoria-Hernández et al reported 133 cases worldwide [ 5 ], with a mortality rate over 95% [ 6 ] due to the difficulty of its diagnosis (CT images of E. histolytica abscesses are indistinguishable from those CT images of abscesses due to other organisms) or due to inadequate treatment, especially if drainage is not performed [ 5 , 6 , 12 , 13 ]. In many published cases of cerebral amebiasis, the diagnosis is made postmortem [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amebic brain abscesses are extremely rare and arise almost exclusively alongside amebic lung or liver abscess [ 2 ]. Victoria-Hernández et al reported 133 cases worldwide [ 5 ], with a mortality rate over 95% [ 6 ] due to the difficulty of its diagnosis (CT images of E. histolytica abscesses are indistinguishable from those CT images of abscesses due to other organisms) or due to inadequate treatment, especially if drainage is not performed [ 5 , 6 , 12 , 13 ]. In many published cases of cerebral amebiasis, the diagnosis is made postmortem [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brain abscess caused by E. histolytica is an infrequent manifestation of amebiasis infection and is most commonly, although not always, observed in patients with a concomitant liver abscess. Around 133 cases have been reported worldwide [ 5 ]. They are very lethal, exhibiting a mortality rate over 95% [ 6 ] due to the difficulty of its diagnosis and inadequate management.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were reported for refractory giardiasis due to MTZ resistance in the parasite in both healthy and immunocompromised individuals ( Morch et al., 2008 ; Nabarro et al., 2015 ; Carter et al., 2018 ; Lalle and Hanevik, 2018 ). So far, there is slight evidence for MTZ resistance in E. histolytica ( Victoria-Hernandez et al., 2020 ), but a decrease in 5-nitroimidazole susceptibility can be induced experimentally ( Wassmann et al., 1999 ; Iyer et al., 2017 ). Notoriously, increased drug resistance leads to higher doses used in the treatment and, therefore, more severe side effects (Hernandez Ceruelos ( Hernandez Ceruelos et al., 2019 ).…”
Section: Treatment and Side Effectsmentioning
confidence: 99%
“…[2,26] En el ámbito clínico, existen múltiples reportes de casos que van desde pancolitis amebiana, absceso hepático y abscesos cerebrales amebianos. [27,28] Por otro lado, G. lamblia representa el protozoo con mayor número de publicaciones en Colima y Jalisco (Tabla 1); sin embargo, la mayor prevalencia se reporta para B. hominis con un 49 % seguido de Cryptosporidium spp. con un 7 %, en este último estado.…”
Section: Zonaunclassified